Efficient Protocol For Shoot Regeneration Via Induction of Embryos Of A Critically Endangered Medicinal Plant Drimiarazii Ansari - CHARUSHILA DALAVI; SWAROOPA PATIL; AVINASH GHOLAVE; S. R. YADAV (International Journal of Pharma and Bio Sciences, 2018)
In Maharashtra the genus Drimia is represented by five species. The genus is mainly used for its cardiotonic properties and is used in case of congestive heart failure. Drimia produces healthy inflorescence but seed setting is rare and it propagates by formation of bulbils at leaf tips. Mainly it contains Bufadienolide compounds, which are widely used as traditional remedies for the treatment of several ailments, like rheumatism, inflammation and disorders associated with the central nervous systems. Out of five species, Drimia razii is endemic to the Maharashtra region. It is critically endangered species. So the formation of alternative sources for the production of these compounds is of prime importance. In vitro regeneration or micropropagation has developed as an alternative tool for the propagation, conservation and rapid multiplication of medicinal plants which are difficult to propagate through conventional methods. It has opened new facets in scaling up of medicinal plant production using different explants. An efficient protocol for somatic embryogenesis via callus formation and somatic embryogenesis has been developed using bulb scale with disc, which were cultured on MS medium supplemented with different concentrations combinations of 2,4-D, NAA and IAA. Maximum callus induction was observed on MS medium augmented with 2,4-D (3 mg/l), NAA (3 mg/l), Kn (3 mg/l) and 15 % coconut milk (CM). It was transferred on MS basal medium in which induction of embryogenesis was observed. These embryos were passed on MS Basal medium containing 3 mg/l BAP for shoot induction. The in vitro plant propagules were afterwards transferred on half strength MS basal medium for root development. Well developed plantlets were shifted on to the hardening mixture consisting 1:1 proportion of coco peat and soil.